Surveillance Study of Klebsiella pneumoniae in the Giant Panda Revealed High Genetic Diversity and Antibiotic Therapy Challenge - Yang Feng; Yaoyan Chen; Songrui Liu; Rong Hou; Xia Yan; Yi Geng; Zhijun Zhong; Hongrui Guo; Ping Ouyang; Dongsheng Zhang; Xiaoyan Su (MDPI AG, 2022)
Klebsiella pneumoniae is not only a worldwide human pathogen, it also effects wildlife, such as the giant panda (Ailuropoda melanoleuca), in which it has recently been evidenced to result in diarrhea, organ failure, and even death. A K. pneumoniae investigation was carried out at the Chengdu Research Base of Giant Panda Breeding in 2018. As part of the investigation, the pulsed-field gel electrophoresis (PFGE) typing, multilocus-sequence typing (MLST), antibiotic resistance profiles (ARPs), and antibiotic resistance genes (ARGs) were studied based on all isolates. Fecal samples were collected from 72 A. melanoleuca from May to December 2018, and a total of 90 K. pneumoniae were isolated from 153 fecal samples. The genotyping results showed that the isolates had high diversity, of which 84 clusters were obtained by PFGE and 57 STs by MLST. The overall trend of the similarity of isolates was the first sample period > second sample period > third sample period, which showed the increasement of genome variability of K. pneumoniae. In addition, 90 isolates showed high resistance to ampicillin, rifampicin, and compound sulfamethoxazole. Of the obtained isolates, 50% carried 6~8 ARPs, and the carrying volume increased during three sample periods, in which we found two isolates carrying 12 and 13 ARPs during the third sample period, respectively. Moreover, a total of 65 ARGs were detected (90.28%, 65/72) in 90 K. pneumoniae samples. Almost all bacteria sampled contained 17 ARGs that belonged to the β-lactamase, Multidrug, MGEs, Aminoglycoside, and Tetracycline, which may be the basis of ARPs of K. pneumoniae. Moreover, the types of Multidrug and MGEs had a greater impact on antibiotic susceptivity of K. pneumoniae. Our results showed that K. pneumoniae has a serious risk of transmission in A. melanoleuca and K. pneumoniae had a high possibility of genome diversity and the risk of drugs tolerance under the large antibiotic usage.